2011
DOI: 10.4137/bcbcr.s6128
|View full text |Cite
|
Sign up to set email alerts
|

Five Methods of Breast Volume Measurement: A Comparative Study of Measurements of Specimen Volume in 30 Mastectomy Cases

Abstract: Background:To compare breast volume measurement techniques in terms of accuracy, convenience, and cost.Methods:Breast volumes of 30 patients who were scheduled to undergo total mastectomy surgery were measured preoperatively by using five different methods (mammography, anatomic [anthropometric], thermoplastic casting, the Archimedes procedure, and the Grossman-Roudner device). Specimen volume after total mastectomy was measured in each patient with the water displacement method (Archimedes). The results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 20 publications
3
134
0
1
Order By: Relevance
“…Mammographic density of ACR levels 1-2 were defined as low density, and levels 3-4 were defined as high density. We measured the volume of the breast using the following formula proposed by Kalbhen et al (1999), which had been demonstrated in previous studies (Kayar et al, 2011): breast volume =π/4 ×(W×H×C), where W=breast width, H=breast height, and C=compression thickness in craniocaudal mammography. Breast width, height and compression thickness were all measured on the craniocaudal mammogram by the computer.…”
Section: Methodsmentioning
confidence: 99%
“…Mammographic density of ACR levels 1-2 were defined as low density, and levels 3-4 were defined as high density. We measured the volume of the breast using the following formula proposed by Kalbhen et al (1999), which had been demonstrated in previous studies (Kayar et al, 2011): breast volume =π/4 ×(W×H×C), where W=breast width, H=breast height, and C=compression thickness in craniocaudal mammography. Breast width, height and compression thickness were all measured on the craniocaudal mammogram by the computer.…”
Section: Methodsmentioning
confidence: 99%
“…This method have the disadvantage of being very time-consuming, since it is necessary to carry out in each axial cut the boundary of the ROI in order to decrease the error. Today's medical software have tools which allow to avoid the delimitation in each cut, automatically completing the ROI, although associated with an increase of the error [38,39]. In addition to the fact that the division being time-consuming, shaping the .stl file of the ROI in CAD software also presents some difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the most significant feature of this study was that the results of both anthropometric methods were compared with their respective mastectomy specimen volumes, which served as controls. There are only five studies that have been conducted with specimen volume as the control [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Forward projection of nipple, measured in centimetres as distance between the sternum and a vertical flat surface touching the nipple, was taken as mammary projection. Volume of breast was calculated by following Anthropometric formulae:-1.Breast circumference based formula by Oteify et al [4] : • Volume = 0.973 (breast circumference in supine / 6.28) 3 • Volume = 1.193 (breast circumference in upright / 6.28) 3 2. Breast radius & projection based formula by Qiao et al [5] :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation